PERBANDINGAN PENGARUH FASHION TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI E-COMMERCE DAN TOKO TRADISIONAL - Hairul Fadil Anam; Febri Ariyantiningsih; Danilmatin Abdalllah; Thoriqul Aman; Hidayat Hidayat (Fakultas Ekonomi dan Bisnis, 2025)
The fashion industry has undergone significant transformation due to rapid advancements in digital technology, particularly with the expansion of e-commerce platforms. Fashion consumption is no longer limited to fulfilling basic clothing needs, but has evolved into a medium for expressing identity, lifestyle, and social values. This study aims to examine and compare the influence of fashion on consumer purchasing decisions in e-commerce and traditional retail stores.This study adopts a descriptive-comparative approach to analyze differences in consumer behavior across online and offline shopping channels. Several factors, including fashion trends, product quality, pricing strategies, promotional activities, accessibility, and shopping experience, are evaluated to determine their impact on purchasing decisions. The results reveal that e-commerce plays a dominant role in influencing consumer decisions through convenience, extensive product variety, price transparency, and digital marketing practices. Conversely, traditional retail stores remain influential due to direct product interaction, personalized services, and higher consumer confidence in product quality.The findings indicate that both distribution channels possess unique strengths in shaping purchasing decisions. Therefore, fashion businesses are encouraged to implement integrated marketing strategies that combine digital capabilities with the experiential advantages of traditional retail in order to sustain competitiveness in the dynamic fashion market